Nanocrystalline composite material and preparation method and application thereof
By adding a silane coupling agent to FENI materials and annealing treatment, combined with FesinbbCu nanocrystal to prepare nanocrystalline composite materials, solve the problem of high magnetic powder core loss and low magnetic guidance rate in the mid -frequency range, and realize the high magnetic guidance rate. Taking into account the performance of low loss.
Patent Information
- Application Number
- CN202411654254.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art, the magnetic powder core has high loss and low permeability in the intermediate frequency range, making it difficult to take into account the performance of low loss and high permeability.
By mixing the FENI material with the sibidane coupling agent and an annealing, then mixed with the Fesinbbcu nano -crystal to perform suppression and secondary annealing to prepare nanocrystalline composite materials. This method optimizes the size and decentralization of the grain and decentralization by controlling the temperature and time of the annealing, improves the magnetic guidance and reduces losses.
In the range of 300-3000kHz, nanocrystalline composite materials show high magnetic conductivity and low loss, suitable for electronic induction devices such as transformers and transformers.
Smart Images

Figure BDA0005141747520000091 
Figure BDA0005141747520000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic material preparation, and specifically relates to a nanocrystalline composite material and a preparation method and application thereof. Background Art
[0002] Nanocrystalline and iron-nickel materials are both magnetic powder core materials, which are widely used in filters, transformers, inductors, capacitors, magnetic devices, medicine, aerospace and other fields. Compared with traditional magnetic materials, the particle size of nanocrystalline and iron-nickel materials is closer to the magnetic domain size, with lower hysteresis loss and eddy current loss, can efficiently convert energy at high frequencies, have high saturation magnetic induction intensity, realize small volume and high power density design, have good stability in a wide temperature range, maintain high magnetic properties in high temperature environment, have a wide frequency range, and cover low-frequency to high-frequency application requirements. With the advancement of technology and in-depth research, nanocrystalline and iron-nickel materials are expected to play a greater role in future applications. The existing technology of mixing nanocrystalline and iron-nickel powder to prepare magnetic materials is relatively cumbersome and is suitable for low-frequency ranges less than 300kHz. When it is applied to the medium-frequency range of 300-3000kHz, the loss is high and the magnetic permeability is low. Summary of the invention
[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the magnetic powder core in the prior art such as high loss and low magnetic permeability in the medium frequency range, thereby providing a nanocrystalline composite material and a preparation method and application thereof.
[0004] To this end, the present invention provides the following technical solutions.
[0005] The present invention provides a method for preparing a nanocrystalline composite material, comprising the following steps:
[0006] (1) FeNi material is mixed with a silane coupling agent, and a pretreated FeNi material is obtained after a first annealing; wherein the first annealing temperature is 650-750° C., and the time is 0.5-2 h;
[0007] (2) The pretreated FeNi material obtained in step (1) is mixed with FeSiNbBCu nanocrystals to obtain a mixed material, which is then pressed and subjected to secondary annealing.
[0008] The heating rate of the primary annealing is 1-5°C / min.
[0009] In step (1), the silane coupling agent includes at least one of vinyl triethoxysilane, trifluoropropyl triethoxysilane, and phenyl triethoxysilane;
[0010] Preferably, the mass ratio of the FeNi material to the silane coupling agent is (90-110):(0.5-4).
[0011] The particle size D50 of the FeNi material is 10-20 μm.
[0012] In the step (2), the mass ratio of the pretreated FeNi material obtained in the step (1) to the FeSiNbBCu nanocrystals is (3-7):(3-7).
[0013] The general formula of the FeSiNbBCu nanocrystal is Fe a Si b Nb c B d Cu e , where a is 62-89, b is 5-15, c is 5-15, d is 0.5-4, and e is 0.5-4;
[0014] The particle size D50 of the FeSiNbBCu nanocrystal is 10-20 μm.
[0015] The pressing pressure is 10-15T / cm 2 ;
[0016] Preferably, the secondary annealing is performed at a temperature of 550-650° C., for a time of 0.5-4 h, and at a heating rate of 1-5° C. / min.
[0017] The step (2) further comprises adding at least one of a silane coupling agent and a binder to the mixture before pressing;
[0018] Preferably, the silane coupling agent is at least one of vinyltriethoxysilane, trifluoropropyltriethoxysilane and phenyltriethoxysilane;
[0019] Preferably, the amount of the silane coupling agent added is 0.5-1wt% of the mixture;
[0020] Preferably, the adhesive is at least one of epoxy resin, phenolic resin, silicone resin, polyester resin and PVB;
[0021] Preferably, the binder is added in an amount of 1-1.5 wt % of the mixture.
[0022] The invention also provides a nanocrystalline composite material prepared by the preparation method.
[0023] The present invention also provides an electronic inductor device, comprising the nanocrystalline composite material prepared by the above preparation method.
[0024] The technical solution of the present invention has the following advantages:
[0025] 1. The preparation method of the nanocrystalline composite material provided by the present invention comprises: (1) mixing FeNi material with a silane coupling agent, and subjecting the mixture to a primary annealing to obtain a pretreated FeNi material; wherein the primary annealing temperature is 650-750°C, and the time is 0.5-2h; (2) mixing the pretreated FeNi material obtained in step (1) with FeSiNbBCu nanocrystals to obtain a mixture, and then pressing and subjecting the mixture to a secondary annealing. The nanocrystalline composite material prepared by the method has high magnetic permeability and low loss in the medium frequency range of 300-3000kHz. Adding silane coupling agent to the iron-nickel material can prevent the iron-nickel material from agglomerating, improve dispersibility and stability, improve surface energy, improve the magnetic permeability and loss performance of the FeNi material, and then annealing the material after the FeNi material and the silane coupling agent are mixed to remove its internal stress, so that the grain size of the nanocrystalline composite material becomes more uniform and fine, improves its magnetic permeability and reduces loss; the annealing temperature is lower than 650°C, resulting in different grain sizes and poor uniformity of the grain size; the annealing temperature is higher than 750°C, and the abnormal growth of the grains will also reduce the uniformity of the grain size; the uniformity of the grain size helps to improve the densification effect during the annealing process, shorten the particle spacing, reduce the annealing temperature, reduce pores and defects, improve the magnetic permeability of the composite material, and reduce loss. The nanocrystalline composite material of the present invention can be used for transformers, mutual inductors, filter inductors, switching power supplies, photovoltaic inverters, etc.
[0026] 2. The preparation method of the nanocrystalline composite material provided by the present invention controls the amount of iron-nickel material and FeSiNbBCu nanocrystals, which can further balance the loss performance and magnetic permeability; if the amount of iron-nickel material is too much, the magnetic permeability will increase but the loss performance will be affected. When the amount of nanocrystals is increased, the loss will be reduced, but the magnetic permeability will be affected.
[0027] 3. The preparation method of the nanocrystalline composite material provided by the present invention is that the iron-nickel material and the silane coupling agent are annealed once at 650-750°C, so that the performance of the iron-nickel material can be fully exerted, and the composite material has a high magnetic permeability, and then the secondary annealing is performed at 550-650°C, so that the FeSiNbBCu nanocrystal can achieve its higher loss performance, and the composite material has low loss, thereby ensuring that the composite material has the advantages of high magnetic permeability and low loss. If the secondary annealing temperature is too high, it will affect the performance of the FeSiNbBCu nanocrystal. DETAILED DESCRIPTION
[0028] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0029] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0030] In order to solve the defect that the magnetic powder core material in the prior art cannot have both low loss and high magnetic permeability in the medium frequency range, the present invention provides the following technical solution.
[0031] In a first aspect, the present invention provides a method for preparing a nanocrystalline composite material, comprising the following steps:
[0032] (1) FeNi material is mixed with a silane coupling agent, and a pretreated FeNi material is obtained after a first annealing; wherein the first annealing temperature is 650-750° C., and the time is 0.5-2 h;
[0033] (2) The pretreated FeNi material obtained in step (1) is mixed with FeSiNbBCu nanocrystals to obtain a mixed material, which is then pressed and subjected to secondary annealing.
[0034] The present invention first adds a silane coupling agent to the iron-nickel material and then performs a second annealing to prevent the iron-nickel material from agglomerating, improve dispersibility and stability, improve surface energy, improve magnetic permeability and reduce loss. If the first annealing temperature is too low, it will affect the grain size and its uniformity, and if it is too high, the grains will grow abnormally and reduce uniformity. Improving the uniformity of the grain size is helpful to improve the densification effect of the annealing process, thereby improving the magnetic permeability and reducing loss.
[0035] As an example, the temperature of the primary annealing is 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, or a range consisting of any two values. The time of the primary annealing is 0.5h, 0.8h, 1h, 1.3h, 1.6h, 2h, or a range consisting of any two values.
[0036] As an optional implementation, the heating rate of the primary annealing is 1-5°C / min. As an example, the heating rate is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or a range consisting of any two values.
[0037] As an optional embodiment, in step (1), the silane coupling agent includes at least one of vinyl triethoxysilane, trifluoropropyl triethoxysilane, and phenyl triethoxysilane;
[0038] Preferably, the mass ratio of the FeNi material to the silane coupling agent is (90-110):(0.5-4). As an example, the mass ratio of the FeNi material to the silane coupling agent is 90:0.5, 95:0.5, 100:0.5, 105:0.5, 110:0.5, 90:1, 90:2, 90:3, 100:1, 100:3, 105:2, 105:4 or a range consisting of any two values.
[0039] As an optional implementation, the particle size D50 of the FeNi material is 10-20 μm.
[0040] As an optional embodiment, in the step (2), the mass ratio of the pretreated FeNi material obtained in the step (1) to the FeSiNbBCu nanocrystals is (3-7): (3-7). As an example, the mass ratio of the pretreated FeNi material obtained in the step (1) to the FeSiNbBCu nanocrystals is 1:1, 3:5, 3:7, 4:7, 5:3, 5:7, 6:3, 6:7, 7:3 or a range of any two values.
[0041] As an optional embodiment, the general formula of the FeSiNbBCu nanocrystal is Fe a Si b Nb c B d Cu e , where a is 62-89, b is 5-15, c is 5-15, d is 0.5-4, and e is 0.5-4.
[0042] It should be noted that a%, b%, c%, d%, and e% are the mass percentages of the respective elements, and a+b+c+d+e=100.
[0043] The particle size D50 of the FeSiNbBCu nanocrystal is 10-20 μm;
[0044] As an optional embodiment, the pressing pressure is 10-15T / cm 2 ;
[0045] Preferably, the secondary annealing is performed at a temperature of 550-650° C., for a time of 0.5-4 h, and at a heating rate of 1-5° C. / min.
[0046] It should be noted that a too high secondary annealing temperature will affect the performance of FeSiNbBCu nanocrystals; annealing the iron-nickel material and the silane coupling agent once at 650-750°C can fully exert the performance of the iron-nickel material and make the composite material have a high magnetic permeability, and then perform a secondary annealing at 550-650°C to enable the FeSiNbBCu nanocrystals to achieve their higher loss performance and make the composite material have low loss, thereby ensuring that the composite material has the advantages of high magnetic permeability and low loss.
[0047] As an optional embodiment, the step (2) further comprises adding at least one of a silane coupling agent and a binder to the mixture before pressing;
[0048] Preferably, the silane coupling agent is at least one of vinyltriethoxysilane, trifluoropropyltriethoxysilane and phenyltriethoxysilane;
[0049] Preferably, the amount of the silane coupling agent added is 0.5-1wt% of the mixture;
[0050] Preferably, the adhesive is at least one of epoxy resin, phenolic resin, silicone resin, polyester resin and PVB;
[0051] Preferably, the binder is added in an amount of 1-1.5 wt % of the mixture.
[0052] In a second aspect, the present invention provides a nanocrystalline composite material prepared by the above method.
[0053] In a third aspect, the present invention provides an electronic inductor device, comprising the nanocrystalline composite material prepared by the above method. It should be noted that, as is well known in the art, electronic inductors include transformers, mutual inductors, filter inductors, switching power supplies, photovoltaic inverters, and the like.
[0054] Example 1
[0055] This embodiment provides a method for preparing a nanocrystalline composite material, comprising the following steps:
[0056] (1) An iron-nickel material with a D50 of 15 μm and a vinyl triethoxysilane coupling agent were mixed in a mass ratio of 100:1, and the mixture was heated to 720° C. at a heating rate of 3° C. / min in a nitrogen atmosphere and then kept at that temperature for 1 h for an annealing treatment to obtain a pretreated iron-nickel material.
[0057] (2) Pretreated iron-nickel material and Fe with D50 of 15 μm 83Si8Nb7B1Cu1 nanocrystals are mixed in a mass ratio of 1:1 to obtain a mixture, and zirconium balls are added to the mixture for dry powder ball milling. The amount of zirconium balls is 20wt% of the mixture. The dry powder ball milling is 10 minutes. Nitrogen is introduced throughout the process to prevent heat and oxidation during the powder ball milling. Trifluoropropyl triethoxysilane coupling agent is added to anhydrous ethanol to prepare a mixed solution, which is added to the ball-milled mixture and continues to be ball-milled for 15 minutes. The amount of silane coupling agent added is 0.5wt% of the mixture, and then poured out until the anhydrous ethanol is completely evaporated and passed through a 100-mesh sieve; then the binder solution is added and stirred until the solvent evaporates and passes through a 60-mesh sieve; the binder is epoxy resin, the solvent is acetone, and the amount of epoxy resin binder added is 1wt% of the mixture. Then at 12T / cm 2 The ring was pressed under nitrogen atmosphere to obtain a ring; the temperature was increased to 620°C at a heating rate of 3°C / min and then kept for 2h to obtain a nanocrystalline composite material.
[0058] Example 2
[0059] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that the temperature of the first annealing in this embodiment is 680°C.
[0060] Example 3
[0061] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that: the pretreated iron-nickel material in this embodiment is 83 The mass ratio of Si8Nb7B1Cu1 nanocrystals is 7:3.
[0062] Example 4
[0063] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that: the pretreated iron-nickel material in this embodiment is 83 The mass ratio of Si8Nb7B1Cu1 nanocrystals is 3:7.
[0064] Example 5
[0065] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that: in step (2) of this embodiment, the amount of silane coupling agent added is 1 wt % of the mixture.
[0066] Example 6
[0067] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that: in step (2) of this embodiment, the amount of silane coupling agent added is 0.8 wt % of the mixture.
[0068] Example 7
[0069] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that the ball milling time after adding the silane coupling agent in step (2) of this embodiment is 10 minutes, instead of 15 minutes in Embodiment 1.
[0070] Example 8
[0071] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that the ball milling time after adding the silane coupling agent in step (2) of this embodiment is 20 minutes, instead of 15 minutes in Embodiment 1.
[0072] Example 9
[0073] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that the temperature of the secondary annealing in step (2) of this embodiment is 550°C.
[0074] Example 10
[0075] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that the temperature of the secondary annealing in step (2) of this embodiment is 580°C.
[0076] Embodiment 11
[0077] This embodiment provides a method for preparing a nanocrystalline composite material, which is different from Embodiment 1 in that the temperature of the secondary annealing in step (2) of this embodiment is 650°C.
[0078] Comparative Example 1
[0079] This comparative example provides a method for preparing a nanocrystalline composite material. The difference from Example 1 is that this comparative example does not perform an annealing treatment on the iron-nickel material, but directly anneals it with Fe 83 Si8Nb7B1Cu1 nanocrystal mixture.
[0080] Comparative Example 2
[0081] This comparative example provides a method for preparing a nanocrystalline composite material, which is different from Example 1 in that the primary annealing temperature in this comparative example is 640°C.
[0082] Comparative Example 3
[0083] This comparative example provides a method for preparing a nanocrystalline composite material, which is different from Example 1 in that the primary annealing temperature in this comparative example is 760°C.
[0084] Comparative Example 4
[0085] This comparative example provides a method for preparing a nanocrystalline composite material, which is different from Example 1 in that in step (1) of this comparative example, no silane coupling agent is added when the iron-nickel material is subjected to a primary annealing.
[0086] Test Case
[0087] The magnetic permeability at 500kHz and the loss at 500kHz / 50Mt of the nanocrystalline composite materials prepared in each embodiment and comparative example were tested using a WK-6500B analyzer and a SY-8218B-H analyzer, respectively. The results are shown in Table 1. The pretreated iron-nickel material obtained in Example 1 was used as control group 1, and the raw material Fe 83 Si8Nb7B1Cu1 nanocrystals were used as control group 2.
[0088] Table 1 Test results of various embodiments and comparative examples
[0089]
[0090]
[0091] According to the above results, the present invention first adds a silane coupling agent to the iron-nickel material, then performs a primary annealing at 650-750°C, and then mixes it with FeSiNbBCu nanocrystals. The composite material obtained after the secondary annealing takes into account both high magnetic permeability and low loss. From comparative examples 1-3, the iron-nickel material is directly mixed with FeSiNbBCu nanocrystals or the primary annealing temperature is too low, the grains are not fully grown and crystallized, the internal stress cannot be completely eliminated, and the agglomeration phenomenon is serious; the primary annealing temperature is too high, causing the grains to grow abnormally, affecting the performance. From comparative example 4, no silane coupling agent is added before the primary annealing, the magnetic permeability becomes lower and the loss increases. This is because the silane coupling agent can make the particles form an interactive structure, improve the interface force and bonding strength, and increase the dispersion, which is beneficial to improve the magnetic permeability and loss performance of the material. From the control group 1-2, the present invention uses the iron-nickel material annealed once and compounded with FeSiNbBCu nanocrystals to obtain a composite material that takes into account both high magnetic permeability and low loss.
[0092] From the above results, the present invention can obtain composite materials that meet the required performance under different ball milling times and different silane coupling agent addition amounts. The magnetic permeability of the nanocrystalline composite material prepared by the present invention is not less than 50H / m, and the loss is not higher than 900mW / cm 3 According to the principle of reducing costs and increasing efficiency, the present invention can obtain a high-performance magnetic powder core composite material in a shorter time and with a lower amount of silane coupling agent.
[0093] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a nanocrystalline composite material, characterized in that: The following steps are involved: (1) FeNi material is mixed with a silane coupling agent, and a pretreated FeNi material is obtained after a first annealing; wherein the first annealing temperature is 650-750° C., and the time is 0.5-2 h; (2) The pretreated FeNi material obtained in step (1) is mixed with FeSiNbBCu nanocrystals to obtain a mixed material, which is then pressed and subjected to secondary annealing.
2. The preparation method according to claim 1, characterized in that: The heating rate of the primary annealing is 1-5°C / min.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the silane coupling agent includes at least one of vinyl triethoxysilane, trifluoropropyl triethoxysilane, and phenyl triethoxysilane; Preferably, the mass ratio of the FeNi material to the silane coupling agent is (90-110):(0.5-4).
4. The preparation method according to any one of claims 1 to 3, characterized in that The particle size D50 of the FeNi material is 10-20 μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step (2), the mass ratio of the pretreated FeNi material obtained in the step (1) to the FeSiNbBCu nanocrystals is (3-7):(3-7).
6. The preparation method according to any one of claims 1 to 5, characterized in that: The general formula of the FeSiNbBCu nanocrystal is Fe a Si b Nb c B d Cu e , where a is 62-89, b is 5-15, c is 5-15, d is 0.5-4, and e is 0.5-4; Preferably, the particle size D50 of the FeSiNbBCu nanocrystals is 10-20 μm.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The pressing pressure is 10-15T / cm 2 ; Preferably, the secondary annealing is performed at a temperature of 550-650° C., for a time of 0.5-4 h, and at a heating rate of 1-5° C. / min.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The step (2) further comprises adding at least one of a silane coupling agent and a binder to the mixture before pressing; Preferably, the silane coupling agent is at least one of vinyltriethoxysilane, trifluoropropyltriethoxysilane and phenyltriethoxysilane; Preferably, the amount of the silane coupling agent added is 0.5-1wt% of the mixture; Preferably, the adhesive is at least one of epoxy resin, phenolic resin, silicone resin, polyester resin and PVB; Preferably, the binder is added in an amount of 1-1.5 wt % of the mixture.
9. The nanocrystalline composite material obtained by the preparation method according to any one of claims 1 to 8.
10. An electronic inductor device, characterized in that: The invention comprises a nanocrystalline composite material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Iron-nickel magnetic powder core and preparation method thereof
CN113948264A
Preparation method of iron-based composite magnetic powder core
CN115083718A
Soft magnetic composite material and preparation method thereof
CN117198674A
High-permeability low-loss nanocrystalline composite magnetic powder core and preparation method thereof
CN117936217A
MAGNETIC MATERIAL COMPRISING FeNi ORDERED ALLOY AND MANUFACTURING METHOD FOR THE SAME
US20200075201A1